TANGGUNGJAWAB PERUSAHAAN PENYEDIA LAYANAN APLIKASI GO-JEK TERKAIT PESANAN (ORDERAN) FIKTIF PENGGUNA LAYANAN APLIKASI GO-JEK TERHADAP DRIVER - Hylda Myrandha Syabai’ni; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
Go-Jek is a company in Indonesia that is engaged in online transportation. Go-Jek is a social technology company that aims to improve the welfare of workers in various informal sectors in Indonesia. The journey of the Go-Jek Application Service Provider Company in fact often causes problems, along with the increasing number of Application Users (orderers / consumers) where Go-Jek service features in the form of Go-Food which cause losses to Go-Jek drivers due to fictitious orders made by Application User (food order). What is the responsibility of the Go-Jek Application Service Provider Company in the event of a fictitious order (order) from the Application User (ordering / consumer) for the driver? This research uses normative legal research methods. This form of accountability is in the form of providing compensation to partners. PT. Karya Anak Bangsa application and PT. The Global Semestaakan Package provides compensation for costs incurred by partners in accordance with the purchase note or receipt if it is proven that in the implementation of services to partner consumers, there is no mistake. This is a form of repressive legal responsibility given to Go-Jek drivers who experience losses due to fictitious orders made by consumers.